2002
DOI: 10.1007/s00125-002-0917-3
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch between insulin-mediated glucose uptake and blood flow in the heart of patients with Type II diabetes

Abstract: Aims/hypothesis. We investigated the effect of physiological hyperinsulinaemia on global and regional myocardial blood flow and glucose uptake in five patients with Type II (non-insulin-dependent) diabetes mellitus and seven healthy control subjects. Methods. Myocardial blood flow was assessed by positron emission tomography with oxygen-15 labelled water (H 2 15 O) either before or after 1 h of euglycaemic hyperinsulinaemia. Myocardial glucose uptake was assessed by positron emission tomography and fluorine-18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Insulin vasodilates skeletal muscle 6, 37 and coronary 38, 39 vasculature. Insulin resistance contributes to endothelial dysfunction in prediabetes (Figure 1).…”
Section: Endothelial Vasodilator Dysfunction In Prediabetesmentioning
confidence: 99%
“…Insulin vasodilates skeletal muscle 6, 37 and coronary 38, 39 vasculature. Insulin resistance contributes to endothelial dysfunction in prediabetes (Figure 1).…”
Section: Endothelial Vasodilator Dysfunction In Prediabetesmentioning
confidence: 99%
“…Since recent studies using positron emission tomography (PET) [6, 7], in contrast to previous studies using coronary sinus catheterization, have demonstrated an increase in myocardial perfusion following insulin administration, we hypothesized that this mechanism is an inherent component of insulin-stimulated MGU. The aim of the present investigation was to study the influence of high physiologic insulinemia on myocardial perfusion and glucose uptake and the involvement of EDNO in healthy volunteers.…”
Section: Introductionmentioning
confidence: 68%
“…Two recent studies have shown a slight vasodilation in the myocardium following local coronary [21]and systemic insulin infusion [6]in patients with coronary artery disease and type 2 diabetes, respectively. Our finding is in accordance with the majority of studies whether coronary sinus flow measurement or PET was used [3, 4, 7].…”
Section: Discussionmentioning
confidence: 99%
“…This is generally demonstrated using positron emission tomography imaging of a radiolabelled glucose analogue that is infused during a euglycemic-hyperinsulinemic clamp. This reduction in cardiac glucose uptake has been demonstrated independent of any limitation in cardiac blood flow, although there is evidence that relative regional perfusion may be altered ( Iozzo et al, 2002b ). Reduced glucose uptake could have significant consequences for cardiac metabolism and therefore performance due to the aforementioned rapid flux and oxygen efficient generation of ATP via glucose metabolism, particularly in the presence of subclinical cardiovascular stress (likely in patients with diabetes).…”
Section: Resultsmentioning
confidence: 99%